2016
DOI: 10.17116/kurort2016338-41
|View full text |Cite
|
Sign up to set email alerts
|

The isokinetic evaluation of the knee joint function following the autoplastic correction of its anterior cross-shaped ligament

Abstract: 1 ФГАОУ ВО «Российский университет дружбы народов», Москва, Россия; 2 ГБОУ ДПО «Российская медицинская академия последипломного образования», Москва, Россия; 3 ГБУЗ «Городская клиническая больница №3», Москва, Россия; 4 ФГБУ «Федеральный научно-клинический центр специализированных видов медицинской помощи и медицинских технологий» ФМБА, Москва, Россия В основе нестабильности коленного сустава лежит дисбаланс мышц-агонистов и мышц-антагонистов, который в результа-те приводит к развитию признаков деформирующего … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In [12][13][14], differences between the injured leg and the healthy leg under preoperative and postoperative surgical examinations were evaluated in terms of the constant velocity attained with ACL reconstruction. The efficiency of ACL reconstruction with postoperative surgery was investigated in [15]; the experimental results showed that time-frequency analysis of various knee joint features can be used to evaluate the status of the knee joint and rehabilitation progression.…”
Section: Introductionmentioning
confidence: 99%
“…In [12][13][14], differences between the injured leg and the healthy leg under preoperative and postoperative surgical examinations were evaluated in terms of the constant velocity attained with ACL reconstruction. The efficiency of ACL reconstruction with postoperative surgery was investigated in [15]; the experimental results showed that time-frequency analysis of various knee joint features can be used to evaluate the status of the knee joint and rehabilitation progression.…”
Section: Introductionmentioning
confidence: 99%